PLAYS AND COUNTERPLAYS: AN INTERTEXTUAL ANALYSIS OF COMMUNIST AND ANTI-COMMUNIST PLAYS IN MALAYALAM THEATRE - Adakkaravayalil Y. Eldhose (Journal of South Asian Studies, 2014)
The current study, which is the first part of a larger project, undertakes how Communism, a political ideology with international ramifications, was represented through political theatre in the context of South India, especially, Kerala. This enquiry will look into both communist and anti-communist manifestations in Malayalam theatre. This project aims to shed some light on a rare series of political plays from Malayalam theatre which was moving parallel to the dominant political ideologies of the state. Sometimes Malayalam theatre favored the communist movement while in some other cases it took anti-communist positions. This series of play texts includes Thoppil Bhasi’s Ningalenne Communistakki (You Made Me a Communist) (1952) asthe source play and Jnanippakkammoonishtavum (I Will Become a Communist Now) (1953) by Kesava Dev, Vishavriksham (Poisonous Tree) (1958) by C. J. Thomas, Ningalaare Communistakki (Whom Did You Make a Communist) (1995) by Civic Chandran, Ningalenne Communistakki Indra Sadassil (You Made Me a Communist in Paradise) (2004) and Enum Ente Thambranum (Me and My Lord) (2008) by Thoppil Soman as counter plays